The Dynamics of the Khalwatiyah Sufi Order in North Luwu, South Sulawesi - Abdain Abdain; Rahmawati Beddu; Takdir Takdir (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2020)
This paper discusses the dynamic of the Khalwatiyah Sufi Order in North Luwu, South Sulawesi. The type of research is qualitative. The research focuses were the dynamic between the leader (caliphs) and followers of the Khalwatiyah Sufi Order. The authors gathered data through library and field research. The techniques to obtain the data were observation, interview, and documentation. The instruments used were interview guidelines, writing instruments, and mobile phones to record audio and video data. The results showed that: 1) The absence of caliphs who guide and teach the Khalwatiyah followers; 2) The assumption of a Khalwatiyah follower said that today's society is modern material life; 3) The absence of regeneration of these Khalwatiyah followers; 4) The young people from the Khalwatiyah family attending tertiary institutions and following various social organizations, they are more likely to develop their organizations than follow the Khalwatiyah ritual. 5) The effect of the environment.